Enhancing Efficiency of Karachi Port (Pakistan) - Shahzad, Dr. Sajid Mehmood (The journal of contemporary issues in business and government, 2022)
Shipping is the driving force for the global economy. Without shipping, worldwide trade would not be practicable. Globalization has increased trade activities and given rise to phenomenal growth and development in maritime transportation. Recent reports suggest that seaports are responsible for over 90 % of world trade. Disorganization in port operations excites a high cost of business, which destroys the economy. There are many ways to gauge the efficiency of ports and there are also several important factors, which require to be analyzed for enhancing the efficiency of ports. The study of port performance and key contributors is not similar for every port, because of different infrastructure and facilities. This research aims to identify and assess the key determinants of performance, which apply to Pakistan’s Karachi Port, and finds out ways to improve upon the delay causative factors for enhancing efficiency.